To find the solution for the system of equations represented in the table, we need to look for a pair of x- and y-values that satisfy both equations: \( y = 2x - 5 \) and \( y = x - 3 \).
Using the values from the table:
-
For \( x = 0 \):
- \( y = 2(0) - 5 = -5 \)
- \( y = 0 - 3 = -3 \)
-
For \( x = 1 \):
- \( y = 2(1) - 5 = -3 \)
- \( y = 1 - 3 = -2 \)
-
For \( x = 2 \):
- \( y = 2(2) - 5 = -1 \)
- \( y = 2 - 3 = -1 \)
- Both equations yield \( y = -1 \).
-
For \( x = 3 \):
- \( y = 2(3) - 5 = 1 \)
- \( y = 3 - 3 = 0 \)
The only pair (x, y) where both equations yield the same y-value is when \( x = 2 \) and \( y = -1 \).
Therefore, the solution for the system is:
(2, -1).